Dyadic Effects of Stress on Family Life Satisfaction in Mothers and Adolescents: Sense of Hope as Mediator - Nayci, Nagihan; Bilmez, Huzeyfe; Ergin, Kemal Feyzi; Maral, Sibel; Satici, Seydi Ahmet (SAGE PUBLICATIONS INC, 2026)
The quality of daily relationships influences life satisfaction, with parent-child interactions playing a central role in shaping family life satisfaction. Yet, limited research has examined how this can be enhanced. This study explores the dyadic effects of maternal and adolescent stress on family life satisfaction, focusing on the mediating role of hope. Data were collected from 1,256 mothers and adolescents, with 372 matched dyads analyzed. Structural equation modeling showed that maternal hope mediates the link between maternal stress and family life satisfaction, with a reciprocal effect found. Maternal and adolescent hope jointly moderated this relationship, indicating significant dyadic effects. Bootstrapping confirmed these results. Both maternal and adolescent stress negatively predicted hope, while higher hope levels in both were associated with greater family life satisfaction. Overall, the findings suggest that hope serves as a protective factor, buffering the negative impact of stress on family life satisfaction in both mothers and adolescents.
Keywords: family life satisfaction; parenting stress; adolescent stress; hope; dyadic effects; structural equation modeling; VALIDATION; ASSOCIATIONS; DEPRESSION; COHESION; ROLES; SCALE; Family Studies